The Influence of Grammarly Application to Improve Students' Writing Skills in Recount Text - Asyifa, Putri Aghna; Daulay, Ernita (Universitas PGRI Semarang, 2024)
Writing proficiency in English is crucial for students, yet errors often occur in their written narratives. This study investigated how the use of Grammarly Application can enhance students' narrative texts. Employing an experimental quantitative research design, the study conducted random sampling among students from a State Middle School in Batubara. The experimental group comprised 31 students who used Grammarly Application, while the control group had 31 students without access to the tool. Pre- and post-tests using writing samples were employed to collect data. The independent sample T-test was utilized to test the hypothesis that Grammarly impacts students' writing skills, yielding a significant result of 0.000 0.05. These findings reject the null hypothesis (Ho) and support the alternative hypothesis (Ha), indicating that Grammarly Application effectively improved students' narrative writing abilities. This study suggested that teachers can utilize Grammarly Application to enhance English writing instruction, enabling students to self-assess and revise their written work more effectively. Grammarly facilitates teachers' provision of constructive feedback and correction on students' writing, thereby enhancing overall writing proficiency in English classrooms. In addition to facilitating self-assessment and revision, Grammarly empowers students with instant feedback on grammar, style, and clarity, fostering a deeper understanding of English language conventions. This automated assistance allows teachers to focus more on higher-order writing skills, such as organization and argumentation, further enriching the learning experience and improving students' overall writing competence in English